2017
DOI: 10.1002/mnfr.201700262
|View full text |Cite
|
Sign up to set email alerts
|

Serine alleviates oxidative stress via supporting glutathione synthesis and methionine cycle in mice

Abstract: Our results indicated that serine supplementation alleviated oxidative stress via supporting glutathione synthesis and methionine cycle, mostly by condensing with homocysteine to synthesize cysteine and providing one-carbon units for homocysteine remethylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 45 publications
6
86
0
Order By: Relevance
“…Moreover, cancer cells cultured in the serine‐deficient medium had reduced glutathione content and were vulnerable to peroxide treatment . Furthermore, our previous studies suggested that serine supplementation could alleviate oxidative stress in different rodent models . Either exogenous or endogenous serine might be important for the synthesis of glutathione and for the cells to counteract oxidative stress, although direct evidence is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cancer cells cultured in the serine‐deficient medium had reduced glutathione content and were vulnerable to peroxide treatment . Furthermore, our previous studies suggested that serine supplementation could alleviate oxidative stress in different rodent models . Either exogenous or endogenous serine might be important for the synthesis of glutathione and for the cells to counteract oxidative stress, although direct evidence is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Research examining the impacts of dietary serine supplementation on humans and rodents showed no adverse effects [4]. Our recent studies with mice showed that serine, as a precursor of glutathione, could alleviate hepatic oxidative stress by regulating the expression of glutathionesynthesis-related genes and increasing glutathione concentration [6,7]. In addition, serine supplementation has been reported to be beneficial for intestinal health in a mouse model with intestinal inflammation and barrier damage induced by lipopolysaccharide (LPS) [8].…”
Section: Introductionmentioning
confidence: 99%
“…NADH production via one-carbon metabolism is driven by serine, which can be generated through the upstream serine biosynthesis pathway in the cytosol ( PHGDH , PSAT1 , PSPH )( Figure 4B ). While enzymes of serine biosynthesis are known to be transcriptionally induced in various stresses (Zhao et al, 2016;Zhou et al, 2017) , we find additional upregulation of ribosome binding and therefore translation for these genes ( Figure 4B; Figure S7 ). We also find such concordant increase in transcription and translation for the mitochondrial one-carbon metabolism enzymes, but not for their cytosolic homologs, supporting our interpretation.…”
Section: Translation Regulation Modulates Energy Metabolism During Ermentioning
confidence: 53%